Dielectric dispersion of copper/rutile cermets: Dielectric resonance, relaxation, and plasma oscillation. (1st January 2021) - Fan, Guohua; Wang, Zhongyang; Ren, Huan; Liu, Yao; Fan, Runhua
Abstract: In this work, dielectric behaviors of dielectric resonance, relaxation, and plasma-like negative permittivity are observed in percolative copper/rutile cermets. Transition for permittivity changing from positive to negative is associated with composition and determined by percolation. The resonance and relaxation responses are related to isolated metallic particles or clusters. Negative permittivity is induced by the plasmonic state of electrons within percolating pathways and dielectric loss of epsilon-negative composites is dominated by conduction loss. Besides, the percolative cermets change from electrical capacitive to inductive with the permittivity transition. Epsilon-negative cermets are expected to be used for electromagnetic shielding and coil-less electrical inductors. Graphical abstract: Image, graphical abstract